Media Narrative About Football Case Study of the Young Garuda U 19 National Team - Suhadi, Suhadi (Journal Humanitarian Responsibilities, Education & Sport Sciences (JHRESS), 2021)
The success of the Garuda Muda U19 team in the 2013 Asean Football Federation (AFF) trophy shocked the eyes of the Indonesian people about their existence. This is a great achievement after 22 years the Indonesian football world has never won a championship. Before the big surprise happened, the talk of Indonesian football could not be separated from the senior Garuda team, which for years had minimal achievements, PSSI conflicts and feuds between national leagues. The name Garuda Muda is almost never in the media discussion. The live final match between Garuda Muda versus Vietnam gathered the attention of the television audience because in their previous AFC match they had always won brilliantly. Not just winning, these young children under the direction of Indra Sjafrie presented exciting performances and unyielding spirits which is as inspirative as football performances in various world football leagues.